Perbandingan Algoritma Convex Hull: Jarvis March dan Graham Scan - Fenina Adline Twince Tobing; Prayogo . (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2020)
Comparison of algorithms is needed to determine the level of efficiency of an algorithm. The existence of a speed comparison in an algorithm that will make a unique shape is sometimes a problem that must be solved by comparing one algorithm with another. This problem can be solved by using Jarvis March and Graham Scan where this algorithm will create a unique shape of a point followed by testing the speed comparison of the two algorithms and the result can be stated that the Graham Scan algorithm in general works faster than the algorithm Jarvis March.